2013
DOI: 10.1002/ange.201304021
|View full text |Cite
|
Sign up to set email alerts
|

Single Glutamate to Aspartate Mutation Makes Ferric Uptake Regulator (Fur) as Sensitive to H2O2 as Peroxide Resistance Regulator (PerR)

Abstract: Kleine Änderung, große Wirkung: Nach Ersatz eines einzigen Glutamatrests durch einen Aspartatrest reagiert der Fe‐Sensor Fur auf H2O2 genauso gut wie der Peroxid‐Sensor PerR. Die In‐vivo‐ und In‐vitro‐Peroxidempfindlichkeiten einer Reihe von PerR‐ und Fur‐Asp/Glu‐Mutanten wurden massenspektrometrisch untersucht. Mit einer Kombination aus Mößbauer‐Spektroskopie und DFT‐Rechnungen ließ sich eine strukturbasierte Begründung für das Verhalten finden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Our findings suggest that the extra space created by the movement of a1 leads to increased propensity of the protein to undergo MCO. These observations are consistent with previous findings showing that decreasing the accessibility of the solvent to the S2 metal-binding site by replacing an aspartate (D104 in BsPerR; D97 in CjPerR) for a glutamate in BsPerR protects the metalloregulator from oxidization [25]. Considering that C. jejuni is a microaerophilic bacterium, it is tempting to speculate that the increased sensitivity of CjPerR, and the reorganization of its first a-helix, renders the protein more susceptible to oxidation and thus more responsive to low ROS levels.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings suggest that the extra space created by the movement of a1 leads to increased propensity of the protein to undergo MCO. These observations are consistent with previous findings showing that decreasing the accessibility of the solvent to the S2 metal-binding site by replacing an aspartate (D104 in BsPerR; D97 in CjPerR) for a glutamate in BsPerR protects the metalloregulator from oxidization [25]. Considering that C. jejuni is a microaerophilic bacterium, it is tempting to speculate that the increased sensitivity of CjPerR, and the reorganization of its first a-helix, renders the protein more susceptible to oxidation and thus more responsive to low ROS levels.…”
Section: Resultssupporting
confidence: 93%
“…The reactivity of the iron‐bound form of PerR to H 2 O 2 varies between species and one element that influences such sensitivity may be the solvent accessibility of the regulatory site. In contrast to biochemical studies performed on Bs PerR , our attempts to purify the nonoxidized form of Cj PerR failed despite the incorporation of chelating agents in the purification buffers and extensive treatment of glassware with dithionite (data not shown). Based on our observation that Cj PerR α1 protrudes out of the V‐shaped dimer (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…S1). The Asp residues (Asp102, Asp102 and Asp104 in FurA1, FurA2 and FurA3, respectively) corresponding to Asp104 of PerR Bs , which is conserved specifically in PerR orthologs and has been suggested to play a crucial role in MCHO (Parent et al ., ), are conserved in the three FurA paralogs of M. smegmatis , reinforcing that the three FurA paralogs belong to the PerR subfamily. Mass spectrometry analyses showed that the short treatment (1 min) of the E. coli strains expressing M. smegmatis FurA proteins with low concentrations (100 μM) of H 2 O 2 led to the oxidation of considerable fractions of the three FurA paralogs by the incorporation of an oxo group into one of two His residues coordinating the regulatory metal (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Of five amino acids comprising the regulatory metal‐binding site, which corresponds to His37, Asp85, His91, His93 and Asp104 of PerR Bs , three His residues are strictly conserved in the Fur family proteins. The Asp residue corresponding to Asp104 of PerR Bs , which is essential for H 2 O 2 sensing through MCHO (Parent et al ., ), is conserved only in the PerR orthologs and actinobacterial FurA proteins. It is substituted by Glu in the Fur orthologs.…”
Section: Resultsmentioning
confidence: 99%
“…However, B. subtilis also employs a true Fur protein whose iron cofactor seems to be resistant to oxidation by H 2 O 2 . Inspection of this discrepancy elicited evidence that in the Fur protein a coordinating glutamate residue probably acts as a bidentate ligand to the iron atom, thereby occluding its sixth coordination site (87). The analogous aspartate ligand of PerR does not.…”
Section: Detecting Hydrogen Peroxide: Oxyr and Perrmentioning
confidence: 99%